Adhesive/silane application effects on bond strength durability to a lithium disilicate ceramic. Issue 4 (15th May 2018) - Romanini‐Junior, Jose C.; Kumagai, Rose Y.; Ortega, Luiz F.; Rodrigues, Jose A.; Cassoni, Alessandra; Hirata, Ronaldo; Reis, Andre F.
Abstract: Objective: To test the effects of different adhesive protocols and silane application on the adhesive durability to a Lithium Disilicate reinforced glass ceramic. Methods: Forty disks of 13 mm diameter (E.max Press) were used. After etching with 9.5% HF for 20 seconds, disks were randomly assigned into 4 groups according to the adhesive/silane protocol: silane application only (SIL); silane application followed by adhesive (SILXP—XP Bond); silane‐containing adhesive (SBU—ScotchBond Universal); silane application followed by silane‐containing adhesive (SILSBU). Four resin composite cylinders of 1‐mm diameter and 3‐mm height were made on each ceramic disk and tested in shear. Specimens were stored in water for 24 hours or 12 months prior to testing. Results were statistically analyzed by two‐way ANOVA and Tukey test. Results: After 24 hours, the highest SBS values were observed for SILXP and SILSBU. However, after 12 months, SILXP and SILSBU presented a significant reduction in SBS, while the highest SBS were observed for SIL. For SBU, no significant reduction in SBS was observed, however, it showed the lowest SBS after 12 months. Conclusions: Regardless of the presence of silane in the composition of SBU, previous silane application is still recommended prior to cementation of Lithium Disilicate. Clinical Significance: The application of silane as a separate step is recommended prior to cementation of Lithium Disilicate reinforced glass‐ceramic, independent of the presence of silane within the universal adhesive solution.